Porous Carbon Black Microsphere from Palm Oil Black Liquor - Jayadi, Jayadi; Maddu, Akhiruddin; Sari, Yessie; Widayatno, Wahyu Bambang; Wismogroho, Agus Sukarto; Firdarini, Cherly; Mulya, Marga Asta Jaya (Jurnal Sains Materi Indonesia, 2023)
The aim of this research is to synthesize porous carbon black microspheres from palm oil black liquor through an in-house spray pyrolysis system. The in-house spray pyrolysis (SP) system was developed using a horizontal furnace. To test the developed SP equipment, the temperature profiles within the developed spray pyrolysis chamber were examined at 3 different setting temperatures (800, 900, and 1000 °C). These temperatures were also applied for synthesizing the carbon black microspheres, with and without nitrogen as carrier gas. The morphology of carbon black produced by using SP equipment was tested by a 3D Optical Microscope and FE-SEM. The optimum temperature obtained in this study is 1000 ºC according to the characterization of carbon black microspheres produced. The FE-SEM analysis indicated the presence of spherical carbon having microstructures. This indicates that the in-house spray pyrolysis machine has been successfully developed for synthesizing carbon black microspheres.